2021
DOI: 10.3389/fimmu.2021.730022
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications of Pulmonary Surfactant Lipids in the Host Defence Against Respiratory Viral Infections

Abstract: Pulmonary surfactant is a complex and highly surface-active material. It covers the alveolar epithelium and consists of 90% lipids and 10% proteins. Pulmonary surfactant lipids together with pulmonary surfactant proteins facilitate breathing by reducing surface tension of the air-water interface within the lungs, thereby preventing alveolar collapse and the mechanical work required to breathe. Moreover, pulmonary surfactant lipids, such as phosphatidylglycerol and phosphatidylinositol, and pulmonary surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Finally, a study showed that the administration of artificial pulmonary surfactant to mice infected with the H1N1 influenza virus in combination with antibody treatment increased the survival rate substantially. This effect was attributed to the surfactant inhibiting alveolar collapse and diffuse alveolar damage in the lungs, thereby preserving lung function for oxygenation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study showed that the administration of artificial pulmonary surfactant to mice infected with the H1N1 influenza virus in combination with antibody treatment increased the survival rate substantially. This effect was attributed to the surfactant inhibiting alveolar collapse and diffuse alveolar damage in the lungs, thereby preserving lung function for oxygenation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…PG and PI thus paly complementary role in innate immune antiviral defense in the lung. Surfactant preparations containing PG can be used for treating respiratory viral infections and potentially for improving lung function in COVID-19 patients ( Bollag and Gonzales, 2020 ; Ji et al., 2021 ).…”
Section: Antimicrobial Potential Of Lipid Classes In Tearsmentioning
confidence: 99%
“…Both mechanisms potentially protect the alveolus by restoring surface tension and alveolar compliance on the one hand, and by reducing fluid accumulation and improving oxygenation on the other hand. Last but not least, the release of surfactant as part of the innate immune system facilitates viral clearance in many ways, as reviewed in detail [ 176 ].…”
Section: Pathophysiology Linked To Ion Channels and Transporters On Lamellar Bodiesmentioning
confidence: 99%